Geometry Optimization as Molecular Modeling on Activating Carbon with Polypirrole. (5th July 2016) - Esquivel Aguilar, Y.C.; Pacheco Sánchez, J.H.
ABSTRACT: Activation of carbon using polypyrrole as activating agent is searched through Molecular Modeling. The Geometry Optimizations carried out helped to observe carbon effect when is attacked by a polymer in order to give an estimation of the pore size diameter of carbon. In this first approximation pore size diameters is about 30 % with respect to BET (Brunauer, P. Emmett y E. Teller) isotherms experimental data.